(untitled) (Docentes 2.0 Journal, 2017)
The Flipped Classroom is a teaching strategy that emerged in 2007 from the hand of Aarom Sams and Jonathan Bergmann, both American teachers. Soon after working together, they realized that many students missed some lessons because they could not attend class for different reasons, one of them the time it took to travel by bus from their homes to the school.